Wajah Baru Literatur Qirā’āt Indonesia: Analisis Kitab Talwīn Syāṭibiyyah Karya Mochamad Ihsan Ufiq - Choirunnisa Choirunnisa; Romlah Widayati; M. Ziyadulhaq (Asosiasi Ilmu Alquran dan Tafsir se-Indonesia, 2024)
This study explores innovative approaches in Talwīn Syāṭibiyyah, a text that employs various color codes to facilitate the learning of qirā’āt, particularly for students at Markaz Qiroat Indonesia (MQI). The primary objective of this research is to analyze how the use of coloration techniques influences learners' comprehension, memorization, and overall engagement during the learning process. Employing a qualitative framework, the study utilizes content analysis of sample texts, footnotes, and user feedback regarding the application of colors—red, green, blue, and cream—that highlight significant aspects of qirā’āt. Data collection methods include interviews with both learners and instructors at MQI, as well as an in-depth review of the text itself. The results indicate that the diverse use of colors aids learners in identifying key elements, such as the rules and variations of recitation. Furthermore, brief explanations accompanying the verses help readers better understand complex segments of the text. However, some participants noted that an excessive number of visual cues may distract from focus, particularly during the memorization process. Nevertheless, the overall reception of Talwīn Syāṭibiyyah has been positive, as it enhances comprehension and improves retention of qirā’āt knowledge. These findings suggest the potential for applying similar methods to other Islamic texts in order to enhance the effectiveness and accessibility of learning.